Performance Profiling: Theoretical Foundations, Applied Implementations and Practitioner Reflections. Issue 4 (2nd October 2021) - Bird, Matthew D.; Castillo, Elmer A.; Luzzeri, Matteo
Abstract: Performance profiling is a theory-driven, client-led assessment method utilized by sport psychology professionals to help uncover important physical, psychological, technical, and tactical factors associated with a client's sport. This holistic technique has been shown to influence a number of psychological constructs important to performance, such as self-awareness and intrinsic motivation. Different variations of the performance profile are available for professionals to use in practice. The aims of this paper are to overview performance profiling and its underpinning theory, provide sport psychology professionals with applied guidelines to implement each version, and discuss practitioner experiences when using different variations of the tool.